Microwave Synthesis of Molybdenum Disulfide Nanoparticles Using Response Surface Methodology for Tribological Application - Thachnatharen Nagarajan; Mohammad Khalid; Nanthini Sridewi; Priyanka Jagadish; Rashmi Walvekar (Nanomaterials, 2022)
We used response surface methodology (RSM) based on the central composite design (CCD) model to optimize the synthesis time and temperature of the molybdenum disulfide (MoS2) nanoparticles using the flexiWAVE microwave. Furthermore, the synthesized MoS2 nanoparticles were used in SAE 20W50 diesel engine oil to study the tribological properties according to ASTM standards using a four-ball tribotester. The optimization result shows that the synthesis temperature and time for the MoS2 nanoparticles in the microwave were ~200 °C and ~15 min, respectively, with a coefficient of friction (COF) and average wear scar diameter (WSD) of 0.0849 and 320 μm. Furthermore, the difference between the experimental and predicted values was minimal (1.88% (COF) and 0.625% (WSD)), which was similar to the optimization model.